ARTISTIC FREEDOM AS A MANIFESTATION OF WILLPOWER - Rujina, Valeria (E-Journal VFU, 2024)
An analysis using the methodology of critical psychology regarding the connection between censorship and social sanction in art and the necessary personality traits to oppose and overcome them. A short look into examples and predispositions of enforced restriction on freedom of speech and efforts on guaranteeing it. Artists’ social contexts, personal coping abilities and ability to stand out as a predictor of willpower – postulated as a lead factor in personal artistic growth and popularity.